A Implementation of Antibiotic Prophylaxis Program for Cesarean Section at Thai Nguyen National Hospital - Thi Thu Thuy, Nguyen; Thanh Hai, Nguyem; Xuan Bach, Nguyem; Thi Thu Huong, Hoang; Chi Cuong, Nguyem; Thi Thuy Van, Pham (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 36 No 4DO - 10.25073/2588-1132/vnumps.4261, 2020)
This study aims to evaluate the effectiveness of the use of antibiotic prophylaxis in cesarean section at Thai Nguyen National Hospital as a first pilot activity of a surgical prophylaxis program. In the study, a randomized controlled trial was designed with two groups: intervention group and control group. Patients characteristics and effectiveness of prophylactic antibiotics for caesarean section were compared. The study results show that the patients’ ages ranged from 18 to 44 years; most of the patients had ASA score of 1; and mean hospital length of stay was statistically significant between the two groups (p<0.05). Regarding the indication of caesarean section, the reason of genital tract abnormalities accounted for the highest proportion. The percentage of the patients switching from prophylactic antibiotic regimens to therapeutic antibiotics in the intervention group was 2%. There was no patient with superficial and/or deep incisional surgical site infections in both groups. The difference in mean number of injections in the two groups was statistically significant (p<0.05). The average cost of antibiotics for each patient in the intervention group and control group were 267.720 VND and 543.871 VND, respectively. The study concludes that the effectiveness of antibiotics prophylaxis for caesarean section: 99% of the patients were without wound infection; hospital length of stay in the intervention group was shorter than the control group; and using prophylactic antibiotics was not only more economical but could also reduce the workload of medical staff, costs of antibiotics and medical supplies. Keywords  Antibiotics prophylaxis, caesarean section, Thai Nguyen National Hospital. References [1] Viet Nam Ministry of Health, National guideline on prevention of surgical site infection, issued with Decision No. 3671/QD-BYT, September 27, 2012 of Viet Nam Ministry of Health, Ha Noi, 2012 (in Vietnamese). [2] Viet Nam Ministry of Health, National guideline on antibiotics use, issued with Decision No.708/QD-BYT, March 2, 2015 of Viet Nam Ministry of Health, Ha Noi, 2015 (in Vietnamese). [3] D.W. Bratzler, K.M. Olsen, et al., Clinical Practice Guidelines for Antimicrobial Prophylaxis in Surgery, American Journal of Health-System Pharmacy 70 (2013) 195 – 283. https://doi.org/10.2146/ajhp120568. [4] R.F. Lamont, J.D. Sobel, et al., Current debate on the use of antibiotic prophylaxis for caesarean section, BJOG: An International Journal of Obstetrics & Gynaecology 118 (2011) 193-201. https://doi.org/10.1111/j.14710528.2010.02729.x. [5] T.V. Khai, Infection rate of surgical incisions and associated factors on women after cesarean section at Dong Nai General Hospital, Scientific Research Project of Dong Nai Hospital, 2015 (in Vietnamese). [6] N.H. Tuan, Study on the use of cefazolin to prevent infection after cesarean section or uterine fibroids surgery at the Institute of maternal and neonatal protection, Master’s thesis, Hanoi University of Pharmacy, 2002 (in Vietnamese). [7] F.M. Smaill, R.M. Grivell, Antibiotic prophylaxis versus no prophylaxis for preventing infection after cesarean section, Cochrane Database Syst Rev 10 (2014) CD007482. https://doi.org/10.1002/14651858.cd007482.pub3.